DEVELOPMENT OF ANDROID-BASED AUGMENTED REALITY (AR) ON CRYSTAL STRUCTURE MATERIALS (ATIKANOTO: Journal of Automotive Engineering Education, 2024)
Interesting learning media can arouse students' interest in learning so that it is easy to understand. Students will gain more concrete knowledge through direct experience, through artificial objects, interactive media, virtual reality media and augmentation. Augmented reality (AR) as a learning medium can create a deeper learning experience through clear visual representation. This research uses a quantitative descriptive approach with the RD Planning, Production and Evaluation (PPE) model according to Richey and Klein. This PPE model is used as an analytical model from the beginning to the end of the research (Sugiyono, 2015). The Android-based Augmented reality (AR) application on crystal structure material was created using Unity 2021 software, with 3 other supporting software. The application has brief content along with augmented reality features of BCC, FCC and HCP crystal structures. The percentage of suitability of material experts for Android-based Augmented reality (AR) applications on crystal structure material is 89.4%. The percentage of suitability of media experts for Android-based Augmented reality (AR) applications on crystal structure material is 89.3%. The results of this application development are in the "Very Feasible" category. The results of assessing user responses to applications resulting from the development of Android-based Augmented reality (AR) on crystal structure material obtained a percentage of 88.4% in the "Very Feasible" category. Next researchers are expected to be able to develop Android-based Augmented reality applications on crystal structure material, such as adding features, appearance and content of the material. Media pembelajaran yang menarik dapat membangkitkan minat belajar peserta didik sehingga mudah dipahami. Peserta didik akan lebih konkret memperoleh pengetahuan melalui pengalaman langsung, melalui benda tiruan, media interaktif, media realitas virtual dan augmentasi. Augmented reality (AR) sebagai media pembelajaran dapat menciptakan pengalaman belajar yang lebih dalam melalui representasi visual yang jelas.Penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan model RnD Planning, Production, dan Evaluation (PPE) menurut Richey dan Klein. Model PPE ini digunakan sebagai model yang bersifat analisis dari awal hingga akhir penelitian (Sugiyono, 2015). Aplikasi Augmented Reality (AR) berbasis Android pada materi struktur kristal dibuat menggunakan software Unity tahun 2021, dengan 3 software pendukung lainnya. Aplikasi memiliki isi materi singkat beserta fitur augmented reality struktur kristal BCC, FCC, dan HCP. Persentase kelayakan ahli materi terhadap aplikasi Augmented Reality (AR) berbasis Android pada materi struktur kristal sebesar 89,4%. Persentase kelayakan ahli media terhadap aplikasi Augmented Reality (AR) berbasis Android pada materi struktur kristal sebesar 89,3%. Hasil Pengembangan aplikasi ini berada pada kategori “Sangat Layak”. Hasil penilaian respon pengguna terhadap aplikasi hasil pengembangan Augmented Reality (AR) berbasis Android pada materi struktur kristal memperoleh persentase sebesar 88,4% berada pada kategori “Sangat Layak” Peneliti berikutnya diharapkan dapat mengembangkan aplikasi Augmented Reality berbasis android pada materi struktur kristal, seperti penambahan fitur, tampilan, dan isi materi.